Chapter L'espressione della relazione concessiva fattuale in italiano e in russo - BIAGINI, FRANCESCA (Biblioteca di Studi Slavistici, 2016)
The aim of this paper is to compare the means of expression of factual concessive relation in Italian and Russian on the basis of a bidirectional parallel corpus. The study of the expression of purposive interclausal relation revealed that loose coordination prevails in Russian while tighter subordination dominates in Italian (Biagini 2012). However, for the expression of concessive relation, the results do not confirm a predominance of juxtaposition or coordination in Russian when compared with Italian.